2012
DOI: 10.1016/j.joca.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary CTX-II concentrations are elevated and associated with knee pain and function in subjects with ACL reconstruction

Abstract: Objective Post-traumatic knee osteoarthritis is prevalent after anterior cruciate ligament reconstruction. Biomarkers that identify individuals likely to develop osteoarthritis, especially symptomatic osteoarthritis, can help target preventative and therapeutic strategies. This study examined the magnitude and change over time in urinary CTX-II (uCTX-II) concentrations shortly after ACL reconstruction, and, secondarily, the associations with knee pain and function. Design Subjects were 28 patients with ACL r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 40 publications
(55 reference statements)
4
52
1
5
Order By: Relevance
“…While this induction is thought to be due to ROS production from XO, it is possible that it is operating through other means, which would explain the lack of association found between CPII and ROS+RNS or carbonyl. While other studies have shown an increase in cartilage degradation with joint trauma as measured by CTx-II [31,34,35], we found no such increase. It is probable that the acute timepoint of most of our injury samples (mean 12 days) is the most likely explanation as collagen degradation products begin to be significantly elevated in the SF about 47 days after injury [36].…”
Section: Discussioncontrasting
confidence: 99%
“…While this induction is thought to be due to ROS production from XO, it is possible that it is operating through other means, which would explain the lack of association found between CPII and ROS+RNS or carbonyl. While other studies have shown an increase in cartilage degradation with joint trauma as measured by CTx-II [31,34,35], we found no such increase. It is probable that the acute timepoint of most of our injury samples (mean 12 days) is the most likely explanation as collagen degradation products begin to be significantly elevated in the SF about 47 days after injury [36].…”
Section: Discussioncontrasting
confidence: 99%
“…Our observations of the present prospective large cohort of patients with ACL rupture (i.e., an increased release of aggrecan ARGS neoepitope resulting from increased aggrecanase activity) extend the findings of 1 longitudinal and several cross-sectional studies of kneeinjured patients in whom levels of aggrecan fragments (6,15) and aggrecan ARGS neoepitope fragments (12)(13)(14) were found to be increased early after injury but to be close to normal later after injury. Our finding of increased urine CTX-II concentrations in the acute phase of ACL injury extend and support findings of prior cross-sectional studies showing an increase of CTX-II in synovial fluid, serum, and urine following knee injury (4,21). The strong positive correlation between urine CTX-II and NTX-I in young adults after 1822 STRUGLICS ET AL knee injury is notable and consistent with suggestions that CTX-II, representing a type II collagen degradation product, may be more closely related to turnover of calcified cartilage and bone than to turnover of hyaline joint cartilage (35).…”
Section: Discussionsupporting
confidence: 90%
“…CTX-II is highly correlated with the occurrence, development, injury degree, bone marrow lesion and osteophyte formation of OA [12,13]. For patients with (ACLR) undergoing anterior cruciate ligament reconstruction, their level of CTX-II decreased with the relief of pain and improvement of physical function, and the decrease of CTX-II content indicated a decrease in the severity of the disease [14]. Based on this, in order to verify the hypothesis that CTX-II and C2C can be used as biomarkers of OA joint of knee joint.…”
Section: Introductionmentioning
confidence: 99%